CONSERVATIVE MANAGEMENT OF ACUTE APPENDICITIS IN BHUJ, KUTCH: A PROSPECTIVE STUDY - JILADIA, ASHOKKUMAR G; PATEL, HARDIK MAHESHBHAI; SONI, HET YOGESH; NAYAK, CHINTAN (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The current research was performed to know the outcome of conservative treatment in acute appendicitis using antibiotic therapy. Methods: The present and prospective research performed at Department of Surgery, Gujarat Adani Institute of Medical Science, Bhuj, Kutch for a duration of 2 years. All subjects diagnosed as acute appendicitis radiologically were enrolled into the research considering inclusion and exclusion criteria. Modified Alvarado score (MAS) was calculated based on clinical symptoms, signs, and laboratory investigations. Injection ceftriaxone and injection metronidazole were given for 48–72 h. Subjects who responded for i.v. antibiotics were switched to tablet ciprofloxacin and tablet metronidazole for 7 days and followed for 6 months. Subjects who did not respond to conservative treatment or had recurrence were classified as treatment failure/recurrence. Results: In the present research, total of 300 subjects were incorporated that comprise of 140 males and 160 females. Tenderness in the right inguinal fossa was observed in all the Subjects. MAS were in between 4 and 6 in 84 subjects and were 7–9 in 216 subjects with an average of 7.30. Thirty-six subjects had complicated acute appendicitis and 264 had uncomplicated acute appendicitis. Conclusion: In general, achievement rate of conservative management according to the present research was 82%. On the other hand, there were 12% failures and 6% recurrences in the current research. One of the major future goals will be to recover diagnosis of appendicitis, particularly the diagnostic capability to distinguish among the various forms of appendicitis.